A 3D POM–MOF composite based on Ni(ΙΙ) ion and 2,2′-bipyridyl-3,3′-dicarboxylic acid: Crystal structure and proton conductivity - Wei, Meilin; Wang, Xiaoxiang; Sun, Jingjing; Duan, Xianying (Journal of solid state chemistry, 2013)
We have succeeded in constructing a 3D POM–MOF, {H[Ni(Hbpdc)(H2O)2]2[PW12O40]·8H2O}n (H2bpdc=2,2′-bipyridyl-3,3′-dicarboxylic acid), by the controllable self-assembly of H2bpdc, Keggin-anions and Ni2+ ions based on the electrostatic and coordination interactions. Interestingly, Hbpdc− as polydentate organic ligands and Keggin-anion as polydentate inorganic ligands are covalently linked transition-metal nickel at the same time. The title complex represents a new example of introducing the metal N-heterocyclic multi-carboxylic acid frameworks into POMs chemistry. Based on Keggin-anions being immobilized as part of the metal N-heterocyclic multi-carboxylic acid framework, the title complex realizes four approaches in the 1D hydrophilic channel used to engender proton conductivity in MOFs. Its water adsorption isotherm at room temperature and pressure shows that the water content in it was 31cm3g−1 at the maximum allowable humidity, corresponding to 3.7 water molecules per unit formula. It exhibits good proton conductivities (10−4–10−3Scm−1) at 100°C in the relative humidity range 35–98%. The corresponding activation energy (Ea) of conductivity was estimated to be 1.01eV. A POM–MOF composite constructed by Keggin-type polyanion, Ni2+ and H2bpdc shows good proton conductivities of 10−4–10−3Scm−1 at 100°C under 35–98% RH. [Display omitted] •A POM–MOF was constructed by combining metal N-heterocyclic multi-carboxylic acid framework and Keggin anion.•It opens a pathway for design and synthesis of multifunctional hybrid materials based on two building units.•Three types of potential proton-carriers have been assembled in the 1D hydrophilic channels of the POM–MOF.•It achieved such proton conductivities as 10−4–10−3Scm−1 at 100°C in the RH range 35–98%.